PERAN ATASE IMIGRASI DALAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI LUAR NEGERI - Pratama, Reza Akbar; Hilmy, Muhadzib Rezki; Berlian, Theresya; Wijanarko, Ervan Fawwaz (Jurnal Ilmiah Kajian Keimigrasian, 2025)
The role of Immigration Attachés is crucial in safeguarding Indonesian migrant workers abroad, especially in dealing with immigration issues, legalprotection, and diplomatic matters. Indonesian migrant workers often face challenges such as visa violations, exploitation, and legal difficulties in their host countries. This article explores the responsibilities of Immigration Attachés in protecting migrant workers, focusing on administrative assistance, legal support, and coordination with local immigration authorities. Immigration Attachés play a key role in resolving issues related to overstaying, illegal employment, and human rights violations, often collaborating with host country governments and relevant international bodies. The main challenges in providing protection include limited resources, the complexity of legal frameworks in different countries, and the increasing number of cases involving Indonesian migrant workers in countries such as Malaysia, Saudi Arabia, and Taiwan. Despite these challenges, the presence of Immigration Attachés helps mitigate the risks faced by migrant workers by facilitating repatriation, offering legal counseling, and ensuring their rights are upheld. This article emphasizes the need for stronger bilateral agreements and better resource allocation to enhance the protection of Indonesian migrant workers abroad. Additionally, it calls for improvements in the training and coordination of Immigration Attachés to address emerging challenges, such as the rise in undocumented labor migration.